ANALISIS EFEKTIVITAS MODEL PEMBELAJARAN PROJECT-BASED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA KELAS VII SMP BOARDING-SCHOOL - Safitri, Sherina Ayu; Rizki, Nanda Arista (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
This study aimed to determine which learning model was effective between Project-Based Learning (PjBL) and conventional learning models and describe the PjBL and conventional models on mathematics learning outcomes regarding data and diagram material in seventh grade SMP Muhammadiyah 5 Samarinda. This research was analyzed with mixed methods. The results showed the PjBL class an average posttest score which was higher than the average of the conventional class, with N-Gain scores of 80% (high criteria) and 49% (medium criteria) respectively. Another thing that proves the PjBL model was effective in improving math learning outcomes was the students' positive response, which was 81% with good criteria. This was also supported by the results of student interviews that they were interested and enthusiastic about learning math-based projects. Based on the research results, the PjBL model was described as a model that can arouse students' learning attention through projects related to daily activities. Therefore, the PjBL model was effectively applied to math learning because the understanding process was easier through real objects. Meanwhile, the conventional model applied was not enough to produce learning outcomes that reached the KKTP.